(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
In this study we attempt to approach Montalban’s oeuvre, specifically the novel Los mares de Sur, from the perspective of travel literature. For this purpose we trace the real and imaginary itinerary of Carlos Stuart Pedrell and Pepe Carvalho within a spatial framework provided by the writer himself, that is Barcelona, and during a specific period, the democratic transition, all aimed at revealing what for a large number of literary critics symbolizes Manuel Vázquez Montalbán’s narrative: “the chronicle of disenchantment”.